EFEKTIFITAS LEMBAGA SENTRA PENEGAKAN HUKUM TERPADU (GAKUMDU) DALAM MENEGAKKAN KEADILAN PEMILU - Agang, Muhammad Ilham (JURNAL AKTA YUDISIA, 2019)
?Abstract?Elections are a tangible form of the concept of democracy which is believed to be one form of carrying out government through a "Party" Democracy which should be a party of people who rejoice and have high expectations of the simultaneous election implementation in 2019. Gakumdu as an integrated law enforcement center has an important role in handling election criminal acts. In Article 486 point (1) of Law No. 7 of 2017 explicitly explained the establishment of Gakkumdu intends to equalize the understanding and pattern of handling election criminal acts by the Bawaslu, the Indonesian National Police, and the Attorney General's Office of the Republic of Indonesia. The Gakkumdu members themselves come from the Indonesian National Police and prosecutors from the Indonesian Attorney General's Office.In this paper the central issue is the effectiveness of the integrated Law Enforcement Center (Gakkumdu) in handling every election crime that occurs in each stage of the 2019 General Elections, including seeing what are the problems faced by the Gakkumdu center and what efforts are being made to strengthen the Gakkumdu center.The holding of elections conducted in Indonesia, evidently the procedures and mechanism of elections also influence changes in behavior of both participants, implementers, organizing elections as well as several government and judicial institutions. As for the objects of the formulation of election criminal offenses as formulated in Law Number 7 of 2017 Concerning General Elections, which are classified in line with several qualifications of actions, such as: Criminal acts aimed at everyone, Criminal acts that can be carried out by KPU officers, KPU Province, Regency / City KPU, PPK, PPS and PPLN, made in crimes aimed at implementing the campaign, Criminal acts aimed at election participants proven to receive donations and / or assistance, Criminal acts aimed at state officials / government officials and judicial institutions , Criminal acts aimed at ballot printing companies.